Selected Lectures of the 12th International Workshop on Neonatology; Cagliari (Italy); October 19-22, 2016 - - (Hygeia Press di Corridori Marinella, 2016)
Selected Lectures of the 12th International Workshop on Neonatology • 10 P PEDIATRICS: NOTES FOR THE FUTURE • Cagliari (Italy) • Cagliari (Italy) • October 19th-22nd, 2016 LECT 1. NEONATAL CONGENITAL HEART DISEASE: WHAT'S NEW? • S. Costa, U. Bottone LECT 2. THE PRETERM NEWBORN INFANT WITH PATENT DUCTUS ARTERIOSUS: TO TREAT IT? HOW TO MANAGE IT? WHEN TO TREAT IT? • C. Cavalli LECT 3. CONGENITAL CARDIOPATHies IN CHILDREN WITH DOWN SYNDROME • P. Neroni, R. Pintus, A. Dessì, M. Carboni, S. Floris, G. Ottonello, V. Fanos LECT 4. FROM FETUS TO ADULTHOOD: THE YOUNG ADULT WITH CONGENITAL HEART DISEASE (ACHD) • M. Chessa, E. Conforti, A. Micheletti, D.G. Negura, L. Giugno, A. Varrica, M. Lorito, A. Giamberti LECT 5. RESEARCH NEWS IN CARDIOLOGY: FROM FETUS TO ADULT PATIENT • P.P. Bassareo LECT 6. ADVANCED SIMULATION IN NEONATOLOGY, MARGIN NOTES ON A METICULOUS TAILORING JOB • A. Cuttano, R.T. Scaramuzzo, M. Ciantelli, E. Sigali, A. Boldrini LECT 7. THORACIC ULTRASOUND IN NEONATOLOGY: PRESENT AND FUTURE • D. De Luca LECT 8. MAGNETIC RESONANCE IMAGING IN NEONATAL ASPHYXIA • M. Marras, A. Lai, L. Saba, P.P. Bassareo, L. Scarciolla, D. Longo LECT 9. INTRAOSSEOUS VASCULAR ACCESS IN PRETERM NEONATES • A. Lai, V. Masile, M. Marras LECT 10. THE EARLY GUT COLONIZATION IN NEWBORNS • G. Biasucci LECT 11. MICROBIOTA AND PROBIOTICS • M. Corpino LECT 12. ORGANIZATION, TRAINING AND CHARACTERISTICS OF COTTOLENGO VOLUNTEERING • L. Marchisio LECT 13. HEALTH SITUATION AND EPIDEMIOLOGY IN THE COTTOLENGO'S MISSIONS • E. Scalabrino LECT 14. MATERNAL AND CHILD SERVICES AND CARING NEEDS • I. Farnetani LECT 15. GIVING BIRTH IN RURAL AFRICA: CHALLENGES AND ADVANCES IN A REFERRAL SITE • G. Gaido LECT 16. COTTOLENGO MISSION HOSPITAL CHAARIA (KENYA): BORN IN A BUSH HOSPITAL • R. Cavallini LECT 17. DENTISTRY IN KENYA, THE STORY OF CHAARIA • G. Farnese LECT 18. VOLUNTEERS NURSES IN CHAARIA • S. Ferrante LECT 19. SURGERY IN THIRD WORLD COUNTRIES: THE EXPERIENCE OF THE COTTOLENGO MISSION HOSPITAL • V. Russo LECT 20. THE HUMAN PLACENTA: THE FLIGHT RECORDER OF PREGNANCY • G. Faa, C. Gerosa, D. Fanni, G. Locci, V. Fanos, P. Van Eyken LECT 21. THE LIMITS OF VIABILITY • A. Papageorgiou LECT 22. THE INFANT BORN TO A DIABETIC MOTHER: EARLY AND LONG TERM CONSEQUENCES • U. Simeoni LECT 23. BIOACTIVE SUBSTANCES IN HUMAN MILK • A. Malamitsi-Puchner LECT 24. PRECISION MEDICINE AND NARRATIVE MEDICINE • G. Donzelli, K.S. McGreevy LECT 25. CRITICAL QUESTIONS ON NUTRITION OF PRETERM INFANTS • F. Mosca, M. L. Giannì, P. Roggero, C. Menis, L. Morlacchi, N. Liotto, B. Bracco LECT 26. NEWBORNS BORN TO MOTHERS WITH IMMUNE THROMBOCYTOPENIC PURPURA • M. Yurdakök LECT 27. GENETIC SURFACTANT DYSFUNCTION • M. Somaschini, S. Presi, M. Ferrari, P. Carrera LECT 28. NON-INVASIVE VENTILATION • C. Moretti, C. Gizzi, P. Papoff, C.S. Barbàra, F. Midulla LECT 29. THE RESPIRATORY DISTRESS SYNDROME (RDS) IN LATE PRETERM INFANTS • C. Dani LECT 30. RESPIRATORY SYNCYTIAL VIRUS PROPHYLAXIS IN SPECIAL POPULATIONS • L. Memo, G. Nicolini LECT 31. SPINAL MUSCULAR ATROPHIES • M.B. Chiarini Testa, S. Caggiano, R. Cutrera LECT 32. PRETERM DELIVERY: CLINICAL AND BIOCHEMICAL ASPECTS • E. Cosmi, S. Visentin LECT 33. PREMEDICATION FOR ENDOTRACHEAL INTUBATION IN THE NEWBORN INFANT • P. Biban, L. Andaloro, S. Spaggiari LECT 34. BRAIN MRI: WHAT'S NEW IN PRETERM INFANTS • L.A. Ramenghi, A. Parodi, M.S. Severino, D. Tortora, A. Rossi LECT 35. INTERSTITIAL STEM/PROGENITOR CELLS DURING KIDNEY DEVELOPMENT • D. Fanni, C. Gerosa, P. Van Eyken, V. Fanos, G. Faa LECT 36. THE RENAL CAPSULE: A NEW STEM CELL NICHE? • C. Gerosa, D. Fanni, P. Van Eyken, G. Faa LECT 37. PODOCYTE CHANGES IN THE EARLY PHASES OF HUMAN KIDNEY DEVELOPMENT SUPPORT THE HYPOTHESIS OF THE PRENATAL ORIGIN OF PODOCYTOPATHIES • G. Locci, M. Desogus, A. Crobe, C. Gerosa, D. Fanni, E. Obinu, A. Sanna, P. Van Eyken, V. Fanos, G. Faa LECT 38. METABOLOMICS IN NEPHROLOGY: FROM THE FETUS TO THE ADULT • V. Fanos, M. Puddu, G. Ottonello LECT 39. MICROARCHITECTURE OF THE HUMAN NEPHROGENIC ZONE: AN UPDATE • G. Faa, C. Gerosa, M. Castagnola, F. Coghe, P. Van Eyken, V. Fanos LECT 40. PRENATAL DIAGNOSIS OF MALFORMATIVE UROPATHIES • G. Monni, A. Iuculano, R. Contu LECT 41. PRENATAL AND POSTNATAL URINARY TRACT DILATION: CLINIC AND ECHOGRAPHIC FOLLOW-UP • G. Ottonello, A. Dessì, P. Neroni, A. Atzei, M.E. Trudu, V. Fanos LECT 42. CAKUT AND THE PEDIATRIC NEPHROUROLOGIST TODAY • G. Masnata, F. Esu, L. Chia, V. Manca LECT 43. RENAL CHANGES IN EXTRARENAL PATHOLOGIES: DOWN SYNDROME AND BETA-THALASSEMIA • E. Obinu, G. Locci, A. Desogus, C. Gerosa, P. Van Eyken, G. Faa LECT 44. DOES THE RABBIT NEPHROGENIC ZONE IN CULTURE REFLECT CAUSES FOR IMPAIRED NEPHROGENESIS? • W.W. Minuth LECT 45. IS THE PLACENTA AN INNOCENT BYSTANDER IN PERINATAL PROGRAMMING? • I. Cetin, G.M. Anelli, C. Novielli, C. Mandò LECT 46. INSULIN SENSITIVITY IN IUGR: FROM PLACENTA TO ADOLESCENCE • M.E. Street, P. Lazzeroni, C. Sartori, F. Cirillo LECT 47. MATERNAL HYPERGLYCEMIA, NEONATAL AND ADULT DISEASE • S. Ottanelli, M.P. Rambaldi, S. Simeone, C. Serena, F. Mecacci LECT 48. PLASTICS AND THE NEWBORN • K. Yurdakök LECT 49. HOW CAN THE INCREASE IN CHILDHOOD CANCER BE EXPLAINED? THE ROLE OF TRANSPLACENTAL AND TRANSGENERATIONAL CARCINOGENESIS • E. Burgio LECT 50. NEW FORTIFIERS FOR THE NEWBORN • E. Bertino, M. Giribaldi, A. Coscia, E. A. Cester, P. Tonetto, C. Peila, A. Varalda, G. Moro, S. Arslanoglu, A. Dessì, A. Noto, L. Cavallarin LECT 51. OLIVE OIL AND MATERNAL AND NEONATAL HEALTH • G. Trapani LECT 52. OBESITY IN CHILDREN: ANTE-, PERI- AND POST-NATAL DETERMINISM • C.O. Mărginean LECT 53. NUTRITION AND CYSTIC FIBROSIS • M. Zanda LECT 54. DIAGNOSTIC AND MANAGEMENT IN DIGESTIVE HEMORRHAGES IN CHILDREN • M. Burlea LECT 55. CESAREAN SECTION: PAST, PRESENT AND FUTURE • S. Dessole, M. Pola, G. Virdis, F. Dessole, G. Capobianco LECT 56. NEONATAL BACTERIAL AND FUNGAL INFECTIONS: WHAT'S NEW? • A. Borghesi, C. Achille, C. Tzialla LECT 57. THALASSEMIA: THE STATE OF THE ART • P. Moi, R. Origa, M. Mingoia, G. Marini LECT 58. VITAMIN D DEFICIENCY: WHAT'S NEW? • R. Antonucci, C. Locci, E. Chicconi, L. Antonucci LECT 59. METABOLOMICS AND AGGRESSION (ACTION PROJECT) • M. Manchia, A. Noto LECT 60. DOCEMUS FOUNDATION: A CONTRIBUTION FOR FINANCING NEW CLINICAL LABORATORIES AND SCHOOL TRAINING PROGRAMS IN LOW-INCOME COUNTRIES • G. Nubile LECT 61. NEW NMR BASED TOOLS FOR CLINICAL AND TRANSLATIONAL RESEARCH WITH FOCUS ON NEWBORNS AND CHILDREN • M. Spraul, C. Cannet, F. Fang, H. Schäfer, F. Trefz LECT 62. METABOLOMICS AND AUTISM • M. Mussap, C. Moretti, A. Noto, V. Fanos LECT 63. BIG DATA, METABOLOMICS AND MICROBIOMICS FROM THE FETUS TO THE ADULT: TOWARDS 10 P PEDIATRICS • V. Fanos, M. Mussap LECT 64. MICROBIOTA AND ASTHMA: "HOT TOPIC" VS. IMPLICATIONS FOR THE PRACTITIONERS • C. Gheonea, M. Gheonea LECT 65. ADDING VALUE TO OBSTETRICS, FROM GENOMICS TO EPIGENETICS: AN ECOLOGICAL PERSPECTIVE • A. Ragusa, A. Svelato LECT 66. IMPLICATION OF METABOLOMICS FOR MATERNAL-FETAL MEDICINE • D. Dudzik, M. Skotnicki, M. Żórawski, R. Revello, J. L. Bartha, A. García, C. Barbas LECT 67. AN ETHICS FOR RELATIONSHIPS IN NEONATOLOGY • J.P. Rességuier LECT 68. DO THE NEW EUROPEAN REGULATIONS HELP NURSES? • R. Galaverna LECT 69. BIRTH AND DEVELOPMENT OF A NEONATAL RESPIRATORY ECMO CENTER: NURSING ASPECTS • C. Baracetti, G. Cavallaro, L. Plevani, F. Mosca LECT 70. LATCH SCORE, MATERNAL PERCEPTION AND SUCCESS OF EXCLUSIVE BREASTFEEDING: THE NURSERY EXPERIENCE IN CAGLIARI • B. Baldussu, A. Fenu, D. Pireddu, D. Lampis, R. Pintus, A. Dessì LECT 71. PRESSURE ULCERS IN THE HOSPITALIZED PRETERM INFANT • E. Dioni, S. Tuccio LECT 72. STABILIZATION AND TRANSPORT OF ASPHYXIATed NEWBORNS TO THE REFERENCE CENTER • S. Altea LECT 73. PERINATAL ASPHYXIA: LESSONS FROM METABOLOMICS • E. d'Aloja LECT 74. NEWS ON THE TREATMENT OF GENETIC DISEASES • A. Selicorni LECT 75. EXPANDED NEWBORN SCREENING FOR INBORN ERRORS OF METABOLISM: THE LYSOSOMAL DISEASES • A.B. Burlina, G. Polo, L. Tonet, A. Favret, M. Zampieri, E. Zanonato, C. Cazzorla LECT 76. GAUCHER DISEASE • A. Pession, W. Morello